Dekandensi Moral Dikalangan Siswa; Revitalisasi Strategi PAI dalam Menumbuhkan Moralitas Siswa - Purnama, Medina Nur Asyifah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of writing this work is to analyze moral decadence among students through revitalizing the pie strategy in fostering student morality. This research uses the library research method to understand moral decadence among students and the role of Islamic Religious Education (PAI) strategies in fostering their morality. Data was collected from various credible written sources, analyzed using content analysis to identify main themes, then synthesized to formulate conclusions and recommendations. The research results are compiled in a report that covers various aspects of the findings and provides practical suggestions for improving the effectiveness of PAI. The results of this work are moral decadence among students, including brawls, narcotics, free sex, and bullying, requiring effective moral and religious education interventions. Exemplary strategies and habituation methods, where teachers are role models, can help students internalize religious and moral values. Good religious education must include character formation and good decision making, which can reduce negative behavior such as drug abuse and internet addiction. Teachers who set examples of good morals and personality and provide positive motivation can help students develop positive behavior. With effective religious education, students can understand and practice religious teachings in their daily lives, reducing moral decadence among students.